2018
DOI: 10.1097/j.pain.0000000000001236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the psychometric properties of 3 pain scales used in the pediatric emergency department: Visual Analogue Scale, Faces Pain Scale-Revised, and Colour Analogue Scale

Abstract: Appropriate pain measurement relies on the use of valid, reliable tools. The aim of this study was to determine and compare the psychometric properties of 3 self-reported pain scales commonly used in the pediatric emergency department (ED). The inclusion criteria were children aged 6 to 17 years presenting to the ED with a musculoskeletal injury and self-reported pain scores ≥30 mm on the mechanical Visual Analogue Scale (VAS). Self-reported pain intensity was assessed using the mechanical VAS, Faces Pain Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 59 publications
0
52
0
1
Order By: Relevance
“…FPS-R, CAS, and VAS are all reliable enough to be used in PERs. However, CAS demonstrated a slightly higher responsiveness and reliability, so the authors recommended CAS for children 6–17 years old [71]. However, no other studies confirming these findings were found.…”
Section: Acute Pain Assessment In Childrenmentioning
confidence: 99%
“…FPS-R, CAS, and VAS are all reliable enough to be used in PERs. However, CAS demonstrated a slightly higher responsiveness and reliability, so the authors recommended CAS for children 6–17 years old [71]. However, no other studies confirming these findings were found.…”
Section: Acute Pain Assessment In Childrenmentioning
confidence: 99%
“…This scale is considered to be reliable and has good psychometric properties, but in a study of 456 children in the pediatric emergency service in Canada, it diverged compared to the visual analogue scales and Color Analog Scale, both of which assessed pain intensity (15) .…”
Section: Discussionmentioning
confidence: 99%
“…We will explore the length of stay for patients in the ED and the length of time to effective analgesia (a vNRS pain score of less than 3). Finally, we will record the children’s self-reported pain intensity using a visual analog scale and the Face Pain Scale-Revised (FPS-R) at all study times [ 25 ].…”
Section: Methodsmentioning
confidence: 99%